THE NEXT creator! / cerita, Elsina Puspita Ningrum Salakay...[et.al]; ilustrasi, Muhammad Iqbal, Muhadzab Hasan; penyunting, Ahmad Mahdi - Elsina Puspita Ningrum Salakay; Muhammad Iqbal; Muhadzab Hasan; Ahmad Mahdi (DAR! Mizan, 2016)
131 hlm. : ilus. ; 21 cm.